GOOD CORPORATE GOVERNANCE DAN MANAJEMEN LABA DI BUMN NON-KEUANGAN - Rini, Rini (Media Akuntansi dan Perpajakan Indonesia, 2021)
earnings management. This research uses audit committee, managerialownership, institusional ownership, and independent commissionersas an indicator of good corporate governance. This research uses 19 samplesof SOE’s company non-financial listed on the IDX in the periode 2015–2019. The sample selection is used by a purposive sampling method. Analysiswas carried out by multiple linear regressions. The result indicated thatinstitusional ownership has a negative effect on earnings management, managerialownership and audit committee has a positive effect on earnings management,and independent commissioners have no effect on earnings management.